2018
DOI: 10.3390/su10082886
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Gaps between the Legislative Tools of Soil Protection in the EU Member States for a Common European Soil Protection Legislation

Abstract: Abstract:To ensure an adequate level of protection in the European Union (EU), the European Commission (EC) adopted the Soil Thematic Strategy in 2006, including a proposal for a Soil Framework Directive (the Directive). However, a minority of Member States (United Kingdom, Germany, France, Austria, and The Netherlands) could not agree on the text of the proposed Directive. Consequently, the EC decided to withdraw the proposal in 2014. In the more than 10 years that have passed since the initial proposal, a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Even if the preservation of the soil is crucial for human well-being and for the sustainability of ecosystems, at present in the EU there is a lack of specific legislation to protect the soil. The attempt promoted by the EU Commission to design a community framework for soil protection, the Soil Framework Directive, was withdrawn in 2014 [16]. Consequently, soil legislation was extremely fragmented across EU countries, governance levels, and policy domains [17,18].…”
Section: Soil Sealing In Europe and Italymentioning
confidence: 99%
“…Even if the preservation of the soil is crucial for human well-being and for the sustainability of ecosystems, at present in the EU there is a lack of specific legislation to protect the soil. The attempt promoted by the EU Commission to design a community framework for soil protection, the Soil Framework Directive, was withdrawn in 2014 [16]. Consequently, soil legislation was extremely fragmented across EU countries, governance levels, and policy domains [17,18].…”
Section: Soil Sealing In Europe and Italymentioning
confidence: 99%
“…SFD was considered an interference in domestic policy. The British and German governments asserted that the EU had no business to regulate soil because it is not a cross-border issue (Stankovics, 2018). It is suggested that notwithstanding a majority of the European countries have no legislative text or framework, it is significant to pay attention to the minority which has enacted their own soil protection policy (Scottish Executive, 2007).…”
Section: Political Conflictsmentioning
confidence: 99%
“…Two papers provide insights about emerging challenges in the formulation and implementation of soil regulations at the national and supranational levels that do not fully address the requirements of sustainable soil management. Stankovics et al [48] investigate the obstacles, differences, and gaps in soil legislation and administration in five European countries (the United Kingdom, Germany, France, Austria, and The Netherlands) that could not agree on the proposal for a Soil Framework Directive in the EU in 2014. This lack of agreement ultimately resulted in the directive being refused.…”
Section: Governance For Sustainable Soil Managementmentioning
confidence: 99%